Retrospective Analysis of Treatment Outcomes and Survival Rates in Oral Squamous Cell Carcinoma Patients - Pankaj Kukreja; Raman Grewal; Annaluru Sri Sasank Tejaswee; Sanjeev Sharma; Anuj Paul Maini; Thara Chandran; Sunil Kumar Gulia (Wolters Kluwer Medknow Publications, 2024)
Background: Because of its high rates of morbidity and death, oral squamous cell carcinoma (OSCC) poses a serious threat to world health. To maximize patient care and direct clinical decision-making, it is important to comprehend treatment results and survival rates. Methods: Treatment results and survival rates for OSCC patients treated at a tertiary care facility between 2010 and 2022 were assessed in this retrospective research. Demographic data, tumor features, treatment options, and follow-up results were all included in the data. The relationships between treatment methods and survival rates were evaluated by statistical analysis. Results: There were 107 OSCC patients in all. Compared to radiation and chemotherapy, surgery had reduced recurrence rates and greater overall survival rates as the most common treatment option. There were notable variations in survival rates across the various treatment regimens (P < 0.05). Conclusion: Surgery is the mainstay. Adjuvant treatments, however, are complementary in the management of illness. The significance of customized treatment strategies based on unique patient attributes and tumor features is highlighted by this study in order to maximize results for patients with OSCC. To confirm these results and investigate cutting-edge treatment approaches, more investigation is necessary.